Several colors of scientific consulting: Ukrainian cases - Artem Artyukhov (Knowledge & Performance Management)
Type of the article: Reflexive Preface The proliferation of unethical scientific consulting practices, particularly in post-Soviet contexts, poses significant threats to academic integrity by transforming legitimate knowledge transfer services into commercialized systems that fabricate academic outputs to meet formal performance metrics rather than supporting genuine research efforts. This study aims to analyze and classify different forms of scientific consulting based on their ethical alignment and function within academic systems, introducing the concept of “scientific consulting mills” as a comprehensive framework for understanding these distorted practices. The study employs qualitative content analysis of Ukrainian and international sources, bibliometric review, and a conceptual typology approach, including a Ukrainian academic landscape case study and a color-coded classification model categorizing service providers based on transparency, legality, and ethical compliance. The analysis reveals that growing demand for formal academic indicators fuels the rise of scientific consulting mills that exploit systemic weaknesses in academic evaluation systems. These mills commodify academic achievements and decouple performance metrics from genuine research contributions, offering services ranging from legitimate professional support to fraudulent activities. The paper includes a case study of the Ukrainian academic landscape, complemented by a classification model (“color-coded” types of scientific consulting) that categorizes service providers and practices based on transparency, legality, and ethical compliance. The proposed “scientific consulting mills” concept offers a broader categorization than existing frameworks, such as paper mills, encompassing diverse services that breach academic ethics while masquerading as legitimate consultancy. This concept provides critical insights for combating academic misconduct. Acknowledgments This study was funded by the European Union grant “NextGenerationEU through the Recovery and Resilience Plan for Slovakia” (No. 09I03-03-V01-00130).